BIM-based fall hazard identification and prevention in construction safety planning. (February 2015) - Zhang, Sijie; Sulankivi, Kristiina; Kiviniemi, Markku; Romo, Ilkka; Eastman, Charles M.; Teizer, Jochen
Graphical abstract: Highlights: A literature review on existing construction safety and BIM solutions is presented. A framework for design and planning of fall protection systems in BIM is introduced. A prototype BIM-based safety hazard detection and prevention algorithm was created. Two case studies tested the feasibility and effectiveness of the developed approach. Open issues and BIM-based safety design and planning commercialization are discussed. Abstract: The applications of Building Information Modeling (BIM) in building design and construction planning are growing rapidly. BIM-based modeling and 4D simulation (3D and schedule) has brought many benefits to safety and logistics applications as well. However, only limited automation in modeling and planning safety processes has been exploited so far. The objective of this study is to investigate how potential fall hazards that are unknowingly built into the construction schedule can be identified and eliminated early in the planning phase of a construction project. A survey of research on construction safety and BIM is presented first. Then, a framework was developed that includes automated safety rule-checking algorithms for BIM. The developed prototype was tested using models including an office and a residential building project in Finland. The first case study highlights the comparison of manual vs. automated safety modeling of fall protective systems. It also describes the details to multiple design and as-built scenarios where protective safety equipment is modeled. The second case study presents results of applying the framework to the project schedule. It specifically simulates fall hazard detection and prevention. The contribution of this work is an automated rule-checking framework that integrates safety into BIM effectively and provides practitioners with a method for detecting and preventing fall-related hazards. Presented are also discussions of open issues regarding commercialization of the developed prototype and considerations which explore what impact it might have on resolving safety issues in the field by extending traditional safety management practices.